Comparative efficacy of Syzygium cumini leaf extract and chemical disinfectants against hospital floor isolates: First report of benzalkonium chloride-resistant Mucor sp. - Haorongbam Joldy Devi, Prathiba Gnanasekaran, Yumnam Asha Devi, Durai Saravanan, Thiyagarajan Gopal, Venkataraman Balakumar, Priya Sathish, Kavitha Nataraja, Blessing Kailas Jeya Sundar, Fidelis Daflin Femi (Journal of Applied Pharmaceutical Science, 2025)
The study aimed to isolate and identify organisms present on various floor surfaces within Sathyabama Dental College and General Hospital by standard microbiological procedures and Vitek MS (Biomerieux) and to compare the antibacterial and antifungal effectiveness of Syzygium cumini leaf extract as a plant-derived disinfectant with three routinely used chemical disinfectants (CD1, CD2, and CD3) by agar well diffusion method. Furthermore, to determine the antibiotic and antimycotic susceptibility of floor isolates by disc diffusion method. A total of 61 organisms were isolated, including 41 bacteria and 20 fungi. The bacterial isolates were identified as Staphylococcus sp., Bacillus sp., Providencia rettgeri, Micrococcus sp., Pseudomonas aeruginosa, and Enterobacter hormaechei, while fungal isolates included Mucor sp., Alternaria alternata, Fusarium oxysporum, Penicillium sp., Aspergillus flavus, and Aspergillus niger. Syzygium cumini extract was effective against all bacterial and fungal isolates, whereas the three chemical disinfectants containing benzalkonium chloride were effective against Staphylococcus sp., Bacillus sp., and Micrococcus sp., but resistant to P. aeruginosa, E. hormaechei, and P. rettgeri. CD1 and CD2 were effective against all fungal isolates except Mucor sp., while CD3 showed resistance to all fungi. Gram-positive bacteria were 100% sensitive to Amikacin and Vancomycin and varying resistant to other tested antibiotics. Gram-negative bacteria were 100% resistant to Nitrofurantoin, with varying resistance to other tested antibiotics. Fungal isolates were 100% resistant to Fluconazole, with varying resistance to other antimycotics. Syzygium cumini extract showed significant antimicrobial activity against the disinfectant-resistant, antibiotic, and antimycotic-resistant isolates, supporting the potential use of S. cumini extract as an alternative, non-toxic, and plant-derived floor disinfectant.
Keywords: Agar well diffusion method, disinfectant resistant organisms, disc diffusion method, plant-derived disinfectant